Intraoperative Dexmedetomidine in Peripheral or Emergency Neurologic Surgeries of Patients With Mild-to-Moderate Traumatic Brain Injuries: A Retrospective Cohort Study - Qin Ding; Xianhe Zhang; Peng Chen (SAGE Publishing, 2020)
Background: Although animal models have demonstrated dexmedetomidine (DEX) as neuroprotective in craniocerebral and subarachnoid injuries, but its role in humans remains to be elucidated. The objectives of the study were to compare plasma brain-derived neurotrophic factor (BDNF), cytokine, and superoxide dismutase levels of patients between those who received intraoperative DEX and those who received intraoperative normal saline (NSE) during peripheral or emergency neurologic surgeries. Methods: Intra- and postoperative data of blood biomarkers and surgical outcomes of patients who underwent peripheral or emergency neurologic surgeries with mild-to-moderate traumatic brain injuries were analyzed retrospectively. Patients received intraoperative DEX group (n = 109) or NSE group (n = 116). Results: At 15 minutes after intubation and before the operation, in the DEX group, plasma BDNF concentration decreased but remained much higher than the NSE group ( P < .0001, q = 15.82). After 24 hours of surgeries, levels of cytokine were higher in the NSE group than the DEX group ( P < .05 for all). Dexmedetomidine increased malondialdehyde ( P < .0001) and superoxide dismutase ( P < .0001) levels in DEX group. Conclusions: Intraoperative infusion of DEX may have a neuroprotective, anti-inflammatory, and antioxidant effects during peripheral or emergency neurologic surgeries. Level of Evidence: III.